Birthing in rural South Australia: The changing landscape over 20 years. (December 2015) - Sweet, Linda P.; Boon, Virginia A.; Brinkworth, Vanessa; Sutton, Sarah; Werner, Allison F.
Abstract: Objective: To map trends in the maternity service availability for rural women in South Australia and identify the frequency of women birthing outside of their region of residence. Design: A retrospective review of birth location for rural South Australian women from 1991 to 2010. Setting: Rural maternity units in South Australia. Participants: Birthing statistics from the Pregnancy Outcomes Statistics Unit in South Australia Main outcome measures: Rural birth statistics, including place of birth in relation to place of residence and location of maternity units. Results: Over 60% of maternity units across rural South Australia have closed since 1991. There has been a rise in the percentage of women birthing away from their usual region of residence, rising from 18% in 1991–1995 to 24% in 2006–2010. Conclusions: This study has revealed that almost one quarter of all women residing in rural South Australia relocate to another area to give birth. This is a significant concern for rural women and their families through the expectation of separation, and for the local health services who might now not have the facilities and skills to manage an unplanned maternity presentation. These concerns need to be considered and addressed in order to provide safe and effective care for child‐bearing women regardless of location.